2022
DOI: 10.3389/fimmu.2022.857025
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Dissection of Epithelial-Immune Cellular Interplay in Acute Kidney Injury Microenvironment

Abstract: BackgroundUnderstanding the acute kidney injury (AKI) microenvironment changes and the complex cellular interaction is essential to elucidate the mechanisms and develop new targeted therapies for AKI.MethodsWe employed unbiased single-cell RNA sequencing to systematically resolve the cellular atlas of kidney tissue samples from mice at 1, 2 and 3 days after ischemia-reperfusion AKI and healthy control. The single-cell transcriptome findings were validated using multiplex immunostaining, western blotting, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…After washing with phosphate-buffered saline (PBS), the samples were enzymatically digested to obtain single-cell suspensions. Following similar procedures previously described ( 57 , 58 ), the samples were minced into <1 mm 3 pieces and digested with 5 ml of digestion buffer containing collagenase IV (2 mg/ml; Sigma-Aldrich) and deoxyribonuclease I (1 mg/ml; Sigma-Aldrich) for 30 min at 37°C. Then, the resulting suspension was mixed with 5 ml of 2% fetal bovine serum (FBS)/PBS and centrifuged at 300 g for 5 min at 4°C to get the cell pellet.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After washing with phosphate-buffered saline (PBS), the samples were enzymatically digested to obtain single-cell suspensions. Following similar procedures previously described ( 57 , 58 ), the samples were minced into <1 mm 3 pieces and digested with 5 ml of digestion buffer containing collagenase IV (2 mg/ml; Sigma-Aldrich) and deoxyribonuclease I (1 mg/ml; Sigma-Aldrich) for 30 min at 37°C. Then, the resulting suspension was mixed with 5 ml of 2% fetal bovine serum (FBS)/PBS and centrifuged at 300 g for 5 min at 4°C to get the cell pellet.…”
Section: Methodsmentioning
confidence: 99%
“…Following similar procedures previously described ( 57 , 58 ), the Single-Cell 3′ Library Kit v3 (10x Genomics) was used for single-cell transcriptome amplification and library preparation according to the manufacturer’s instructions. The sorted single-cell suspension was loaded onto a microfluidic chip from 10x Genomics to generate the cDNA library.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sepsis is defined as end-organ dysfunction due to the host’s inflammatory response to infection, in which the damaged kidney, a major source of inflammatory chemokines, may have local and remote deleterious effects on the body and increase the risk of mortality in patients with sepsis ( 3 ). Several studies have shown that the occurrence and development of SA-AKI are closely related to the infiltration of various immune cells ( 31 ). AKI is characterized by inflammatory infiltration within the kidney that induces apoptosis and promotes tubular epithelial cell loss ( 32 ).…”
Section: Discussionmentioning
confidence: 99%